2019
DOI: 10.1152/ajpregu.00316.2018
|View full text |Cite
|
Sign up to set email alerts
|

Low-protein and methionine, high-starch diets increase energy intake and expenditure, increase FGF21, decrease IGF-1, and have little effect on adiposity in mice

Abstract: Low-protein diets most often induce increased energy intake in an attempt to increase protein intake to meet protein needs with a risk of accumulation as fat of the excess energy intake. In female adult BALB/c mice, a decrease in dietary casein from 20% to 6% and 3% increased energy intake and slightly increased adiposity, and this response was exacerbated with soy proteins with low methionine content. The effect on fat mass was however limited because total energy expenditure increased to the same extent as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
45
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 76 publications
7
45
1
1
Order By: Relevance
“…And although BAT Ucp1 mRNA was not increased by the low-protein diet in this study, energy intake and EE were both increased by the low-protein diet (40). The common feature of both studies is that female mice responded to the low-protein diet by preserving their fat mass at the expense of lean tissue, and when the diet produced weight loss, lean tissue was the affected tissue component (15,40). In contrast, male mice preserved lean mass on the low-protein diet and lost fat mass (15).…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…And although BAT Ucp1 mRNA was not increased by the low-protein diet in this study, energy intake and EE were both increased by the low-protein diet (40). The common feature of both studies is that female mice responded to the low-protein diet by preserving their fat mass at the expense of lean tissue, and when the diet produced weight loss, lean tissue was the affected tissue component (15,40). In contrast, male mice preserved lean mass on the low-protein diet and lost fat mass (15).…”
Section: Discussioncontrasting
confidence: 64%
“…The sex‐specific differences in response to the low‐protein diet were attributed in part to a blunting of the diet‐induced increase in plasma FGF21 in females and a lack of induction of BAT and IWAT Ucp1 mRNA by the low‐protein diet . Chaumontet et al conducted a slightly longer protein restriction study with younger female BALB/c mice and found that fat mass was unchanged after 8 weeks of the low‐protein diet, whereas lean mass was significantly decreased, accounting for essentially all of the BW loss over this period. And although BAT Ucp1 mRNA was not increased by the low‐protein diet in this study, energy intake and EE were both increased by the low‐protein diet .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other researchers have investigated food intake in low-protein diets, but they provided inconsistent results. Our results on food consumption corresponded with the findings of www.nature.com/scientificreports/ Larson et al 12 , but are contrary to the other research in which an increase in food consumption was reported 13,14 . Inconsistent results across numerous studies are difficult to fully explain, but may reflect differences in age, sex and breed.…”
Section: Discussionsupporting
confidence: 63%